2006
DOI: 10.1109/tcapt.2006.881762
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of a Miniature-Scale Refrigeration System for Electronics Cooling

Abstract: A miniature-scale refrigeration system suitable for electronics cooling applications was developed and experimentally investigated. A detailed review of the literature on refrigeration systems and system simulation models for application to electronics cooling is also provided. Experimental results obtained with the prototype system demonstrate its feasibility for use in cooling compact electronic devices. The cooling capacity of the system investigated varied from 121 to 268 W, with a COP of 2.8 to 4.7, at pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 5 publications
1
52
1
3
Order By: Relevance
“…Trutassanawin et al (2006) reviewed the available technologies for vapor compression systems in electronics cooling. Several prototype systems were discussed but there appeared to be no commercially viable solutions which are complete miniature systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trutassanawin et al (2006) reviewed the available technologies for vapor compression systems in electronics cooling. Several prototype systems were discussed but there appeared to be no commercially viable solutions which are complete miniature systems.…”
Section: Introductionmentioning
confidence: 99%
“…In particular the compressor is a critical component which can greatly affect the overall size and performance of the refrigeration system, as shown by Trutassanawin et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Trutassanawin et al [6] designed, built and evaluated the performance of a miniature-scale refrigeration system (MSRS) suitable for electronics cooling applications. It was concluded that, although COP's in the order of 1.9-3.2 were obtained, a suitable control strategy was required to improve its performance.…”
Section: Introductionmentioning
confidence: 99%
“…Miniature-scale vapor compression refrigeration systems have received increased recent attention for use in electronics-cooling applications (Trutassanawin et al, 2006). An 3 electrostatically actuated diaphragm compressor offers promise for use in miniature-scale vapor compression systems because of its potential for high efficiency, compactness and…”
Section: Introductionmentioning
confidence: 99%